2008
DOI: 10.3168/jds.2008-1018
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationship of Body Energy and Blood Metabolites with Reproduction in Holstein Cows

Abstract: Body condition score (BCS), energy content (EC), cumulative effective energy balance (CEEB), and blood serum concentrations of glucose, β-hydroxybutyrate (BHBA), and nonesterified fatty acids (NEFA) were measured throughout first lactation in 497 Holstein cows raised on a large commercial farm in northern Greece. All these traits are considered to be indicators of a cow's energy balance. An additional measure of BCS, EC, and blood serum glucose, BHBA, and NEFA concentrations were taken approximately 2 mo (61 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 32 publications
6
28
0
Order By: Relevance
“…Genetic correlations were rather similar with all four traits (Figure 6), the highest estimates being with energy balance (20.64) and energy content (20.60) at the end of lactation. The latter is consistent with the range of weekly correlations (20.66 to 20.74) reported by Oikonomou et al (2008), despite their estimates being derived from a different methodology (genetic regression of DC on energy content) and pertaining to the first lactation cows. Genetic correlations between DC and BCS ranged from 20.30 to 20.53 in agreement with an average correlation of 20.46 reported by Veerkamp et al (2001) and an estimate of 20.30 between single-observation BCS and days open found in Dechow et al (2004).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Genetic correlations were rather similar with all four traits (Figure 6), the highest estimates being with energy balance (20.64) and energy content (20.60) at the end of lactation. The latter is consistent with the range of weekly correlations (20.66 to 20.74) reported by Oikonomou et al (2008), despite their estimates being derived from a different methodology (genetic regression of DC on energy content) and pertaining to the first lactation cows. Genetic correlations between DC and BCS ranged from 20.30 to 20.53 in agreement with an average correlation of 20.46 reported by Veerkamp et al (2001) and an estimate of 20.30 between single-observation BCS and days open found in Dechow et al (2004).…”
Section: Discussionsupporting
confidence: 76%
“…Prolonged periods of negative energy balance have been associated with digestive and locomotive problems (Collard et al, 2000), metabolic disorders (Goff and Horst, 1997), udder-health issues (Banos et al, 2006) and reduced reproductive performance (Reist et al, 2003;Dechow et al, 2004;Oikonomou et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In high-producing dairy cows, lengthy periods of excessive negative energy balance (EB) have been linked to problems such as reduced reproductive performance (Oikonomou et al, 2008;Cutullic et al, 2012), digestive and locomotive disorders (Collard et al, 2000), and metabolic diseases (Goff and Horst, 1997). Therefore, the ability to assess the EB for individual cows in real-time and on farm would be a highly desirable management tool, enabling the dairy farmer to rapidly detect excessive negative EB.…”
Section: Introductionmentioning
confidence: 99%
“…Cows in severe NEB had higher NEFA levels and a longer interval to first ovulation (Roche et al, 2000). Oikonomou et al (2008) reported a negative genetic correlation between NEFA or BHBA concentration and first-service conception rate. Moreover, a positive genetic correlation between body condition score and first-service conception rate has been reported (Veerkamp et al, 2001;Oikonomou et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Oikonomou et al (2008) reported a negative genetic correlation between NEFA or BHBA concentration and first-service conception rate. Moreover, a positive genetic correlation between body condition score and first-service conception rate has been reported (Veerkamp et al, 2001;Oikonomou et al, 2008). High-merit dairy cows had delayed first ovulation and commencement of normal luteal activity compared with lowmerit cows, in association with lower plasma glucose and insulin concentrations (Gutierrez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%